PERANAN HUKUM PIDANA DALAM MENANGGULANGI BULLYING DAN KENAKALAN REMAJA DI DESA HARGO PANCURAN LAMPUNG SELATAN - Achmad, Deni; Fardiansyah, Ahmad Irzal; Tamza, Fristia Berdian; Farid, Muhammad; Trijayanti, Dita (FT Universitas Lampung, 2025)
Children as part of the younger generation are the successors of the ideals of the nation's struggle and human resources in national development. In order to realize quality Indonesian human resources who are able to lead and maintain the unity and integrity of the nation within the framework of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution, continuous development is needed for the sake of survival, growth and physical, mental and social development and protection from all possibilities that will endanger them and the nation in the future. In various ways, these development and protection efforts are faced with problems and challenges in society and sometimes behavioral deviations are found among children, even more than that there are children who commit unlawful acts without knowing their social and economic status. The massive act of bullying has certain consequences for the victims. Bullying in some cases has its own implications towards acts that are included as criminal acts. This study aims to understand the regulation of bullying in Indonesian criminal law and criminal law policies in cases of bullying and juvenile delinquency in Indonesia. The approach method used in this Community Service is through the lecture method in delivering the material, then at the end of the event a question and answer session is held. With this question and answer method, the public is given the opportunity to ask questions according to the theme or relevant questions. The benefit of holding this activity is to create better legal awareness in society so that every member of society realizes and appreciates the importance of the role of criminal law in overcoming bullying and juvenile delinquency.